الهجاء في ديوان الشاعر عمرو عيسى التندميرتي - لشهب, ناجي (Sharwes Scientific Journal, 2025)
The study highlighted the poeticism of the post Amr Issa AL-andimirt; One of the symbols of reform in Mount Nafusa before the Italian occupation of our beloved country through studying the  atirical poems in the poet's collections, represented in two poems, the first satirizing the people of his village for not following the revealed truth, and the second poem in which the poet satirized a person called Abu Nasral-Shami who worked as a judge in the city of Nalut shortly before The Italian occupation, which satirized and insulted the people of the mountain, and also insulted its sheikh and role model, AbdullahAl-Barouni.The poet was sincere in his feelings and did not fear, for God’s sake, the blame of the critic, which made most of his poems very close to our reality, and imitate the situation of many, and as a way of contributing to highlighting Libyan literature, and showing the efforts Its creators, and to have a presence within Arabic literature.